Investigation of mechanical properties of dissimilar joint of Al6063 aluminium alloy and C26000 copper alloy by ultrasonic assisted friction stir welding. (2022) - Chowdhury, Ivy; Sengupta, Kaushik; Maji, Kaustav Kumar; Roy, Swapna; Ghosal, Sujit
Abstract: An attempt by this experiment has been made to analyse the difference of mechanical properties in welding among Friction Stir Welding (FSW) and Ultrasonic assisted Friction Stir Welding (UAFSW). Dissimilar metals 6063 Aluminium Alloy with C26000 Copper alloy are joined in this experiment. Optimum mechanical properties obtained by FSW and UAFSW by calibrating tool rpm range from 400 to 600 rpm with tool transverse rate from 15 to 25 mm/min were obtained and compared. For UAFSW calibration of tool rpm ranges from 400 to 600 rpm tool transverse rate from 15 to 25 mm/min assisted by ultrasonic frequency ranging from 10 to 14 kHz were used. An improvement in the mechanical property observed by addition of the ultrasonic energy to FSW process and been presented in the paper and the ultrasonic vibration used in the study has been observed to be suitable in the range of 10–14 khz for joining dissimilar material under study. Also, an improvement of mechanical properties from 10 to 25 % been observed by addition of the ultrasonic energy to FSW process. The comparative results of the UTS, YS and elongation were explained and presented for FSW and UAFSW process showing the improvement in the material property due to the addition of Ultrosonic energy.